2018
DOI: 10.1111/idj.12380
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric oral pathology in Thailand: a 15-year retrospective review from a medical teaching hospital

Abstract: This study from a medical institution shows a somewhat different spectrum of paediatric oral pathology compared with that reported from dental institutions. While some of the lesions may not be treated by dentists, they still need to be aware of these lesions because affected patients can still present initially to a dentist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 13 publications
(72 reference statements)
3
15
0
4
Order By: Relevance
“…Besides, differences in study design, sample size, period of study, and age-range stratification. The prevalence of conditions in this study generally increased with age, probably due to the nature of the conditions; also the awareness of the older children about their conditions, this result consistent with Taweevisit et al (2018) and Bessa et al (2004), a study in 1211 Brazilian children, the frequency of oral conditions increased with age, in which some of them were associated with habits and systemic problems. In general, OC was reported as most frequent affected site (32.7%) in the current study, while in an American (Shulman, 2005) and Jordanian (Hussein et al, 2017) studies, the lip and tongue were the most affected site 30.70 and 35.9%, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Besides, differences in study design, sample size, period of study, and age-range stratification. The prevalence of conditions in this study generally increased with age, probably due to the nature of the conditions; also the awareness of the older children about their conditions, this result consistent with Taweevisit et al (2018) and Bessa et al (2004), a study in 1211 Brazilian children, the frequency of oral conditions increased with age, in which some of them were associated with habits and systemic problems. In general, OC was reported as most frequent affected site (32.7%) in the current study, while in an American (Shulman, 2005) and Jordanian (Hussein et al, 2017) studies, the lip and tongue were the most affected site 30.70 and 35.9%, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Cross-sectional studies are important in estimating the prevalence of OC and in identifying highrisk individual. In this study, the male:female ratio was (1.04:1), slight male predominance had been noticed, agree with studies (Cavalcante et al, 2016, Ha et al, 2014and Patil et al, 2017, and disagree with Taweevisit et al (2018) and Ambika et al (2011) both showed slight female predominance. The prevalence of oral conditions in this study was 54.4% which was higher than reported in the nearby countries such as Turkey (26.2 %) (Parlak et al, 2006) and Iran (28%) (Jahanfar et al, 2012), possibly because the sample of the current study was from a dental center and not from general hospital, beside; high number of subjects was examined, but it was lower than a study done in India (Ambika et al, 2011), in which 1003 children 4-14 years were included in the study, the prevalence was 64.11%.…”
Section: Discussionsupporting
confidence: 77%
“…The review analysed data from 34 studies for a total of 40,522 biopsies performed (Abdullah, Qader, & OA and Mussedi OS, ; Ataide et al, ; Bataineh & Al‐Dwairi, ; Cavalcante, Turatti, Daniel, Alencar, & Chen, ; Chen, Lin, Huang, Lin, & Yan, ; Chidzonga, Lopez, & Portilla Alvarez, ; Colaci & Sfasciotti, ; Das & Das, ; Dhanuthai, Banrai, & Limpanaputtajak, ; Gultelkin, Tokman, & Turkseven, ; Ha, Kelloway, Dost, & Farah, ; Jaafari Ashkavandi, Ahmadi Sheshdeh, & Kamali, ; Jones & Franklin, ; Keszler, Guglielmotti, & Dominguez, ; Krishnan, Ramesh, & Paul, ; Kwok, Dovigi, Eversole, & Dovigi, ; Lapthanasupkul, Juengsomjit, Klanrit, Taweechaisupapong, & Poomsawat, ; Lawoyin, ; Lei et al, ; Lima Gda et al, ; Maaita, ; Maia, Merly, Castro, & Gomez, ; Martins‐Filho et al, ; Melo, ; Mieko, ; Munsamy, Mahomed, & Rikhotso, ; Seyedmajidi, Hamzehpoor, & Bagherimoghaddam, ; Shah, Le, & Carpenter, ; Sixto‐Requeijo, Diniz‐Freitas, Torreira‐Lorenzo, Garcia‐Garcia, & Gandara‐Rey, ; Sklavounou‐Andrikopoulou, Piperi, Papanikolaou, & Karakoulakis, ; Sousa, Etges, Correa, Mesquita, & Araujo, ; Taweevisit, Tantidolthanes, Keelawat, & Thorner, ; Wang, Chang, Chang, Huang, & Guo, ; Zuniga, Mendez, Kauterich, & Paniagua, ). Overall, the most common biopsied lesions were mucoceles (17.12%), fibrous lesions (9.06%) and pyogenic granulomas (4.87%).…”
Section: Resultsmentioning
confidence: 99%
“…소아 청소년의 구 강 병소에 관한 기존의 연구들은 대부분 종양을 비롯한 특정 질 환에만 초점을 두고 있으며 [2][3][4], 전반적인 구강 병소의 생검 결 과를 보고한 연구는 많지 않다. 북미 [5][6][7][8], 남미 [9][10][11][12][13][14][15], 유럽 [16][17][18], 아프리카 [19,20], 호주와 뉴질랜드 등 전 세계 각 지역에서 소아 청소년 환자의 구강 병소 생검 결과를 후향적으로 분석하 였으며 [21][22][23], 아시아에서는 태국 [24][25][26], 인도 [27], 사우디아라 비아 [28], 이란 [29], 대만에서 주로 연구되었다 [30][31][32]. 국내에서 는 치성 종양에 한정하여 전 연령대에서 시행된 생검 결과에 관 한 연구는 보고된 바 있으나 [33] 계를 고려하고 선행 연구의 연구 설계를 참고하여 세 집단으로 나누었다: 1) 0 -5세(유치열기); 2) 6 -11세(혼합치열기); 3) 12 -16세(영구치열기) [6,8,14,18,19,24,26].…”
Section: ⅰ 서 론unclassified